A high-resolution numerical simulation of the “7.19” extraordinary heavy rainfall in Henan Province under topographic effect - Li, Han; Xi, Le; Wang, Xin-Min (Frontiers in Earth Science, 2023)
Introduction: In this study, based on the ERA5 dataset, the orographic precipitation characteristics during an extraordinary heavy rainfall event in Henan Province on 19 July 2016 are analyzed. Methods: In addition, by using the WRF model and the NCEP GDAS/FNL dataset, a high-resolution numerical simulation is carried out, including a series of sensitivity experiments on the Taihang Mountains, Yunmeng Mountain, and low-altitude areas. Results and Discussion: The distribution of observed precipitation shows that the precipitation over the Taihang Mountains in northern Henan during the daytime on July 19 is significantly enhanced due to the topographic effect compared with that over the plain on the east. The simulation results demonstrate that the distribution of simulated precipitation over the steep terrains on the east side of the Taihang Mountains is closer to the observational precipitation when SRTM-90m is introduced to the WRF model. When the altitude of the Taihang Mountains is lowered by 50%, the accumulated precipitation along the Taihang Mountains in the daytime on July 19 decreases by 26%, accompanied by the northward movement of the heavy precipitation center over the northern Taihang Mountains. In addition, Yunmeng Mountain plays an important role in blocking or diverting the easterly and southeasterly low-level jet. When the terrain elevation of Yunmeng Mountain is reduced, the convergence zone of the wind field in the low level moves to the areas along the Taihang Mountains, which leads to the expansion of the area with heavy rainfall, with the average accumulated precipitation in mountain areas increasing by 7%. In addition, when the low altitude terrain in the study region is reduced by 50%, the center of heavy precipitation obviously moves westward. Combined with the diagnostic analysis of the topographically forced vertical velocity, the results show that the uplift of the low-level jet caused by the low-altitude terrain in northern Henan is one of the reasons that affect the location of the heavy rainfall center.